2016
DOI: 10.18632/oncotarget.13939
|View full text |Cite
|
Sign up to set email alerts
|

Tianshengyuan-1 (TSY-1) regulates cellular Telomerase activity by methylation of TERT promoter

Abstract: Telomere and Telomerase have recently been explored as anti-aging and anti-cancer drug targets with only limited success. Previously we showed that the Chinese herbal medicine Tianshengyuan-1 (TSY-1), an agent used to treat bone marrow deficiency, has a profound effect on stimulating Telomerase activity in hematopoietic cells. Here, the mechanism of TSY-1 on cellular Telomerase activity was further investigated using HL60, a promyelocytic leukemia cell line, normal peripheral blood mononuclear cells, and CD34+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Chinese herbal medicine Tianshengyuan-1 (TSY-1) has been recently shown to increase telomerase activity in normal peripheral blood mononuclear cells and CD34+ hematopoietic stem cells with innately low telomerase activity but to decrease telomerase activity in human promyelocytic leukemia (HL60) cells with high intrinsic telomerase activity. Genome screening analysis identified TERT as potential target gene associated with the TSY-1, possibly via the methylation of TERT promoter (191).…”
Section: Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese herbal medicine Tianshengyuan-1 (TSY-1) has been recently shown to increase telomerase activity in normal peripheral blood mononuclear cells and CD34+ hematopoietic stem cells with innately low telomerase activity but to decrease telomerase activity in human promyelocytic leukemia (HL60) cells with high intrinsic telomerase activity. Genome screening analysis identified TERT as potential target gene associated with the TSY-1, possibly via the methylation of TERT promoter (191).…”
Section: Natural Productsmentioning
confidence: 99%
“…However, overall benefit is rather limited. One of the reasons might be the regulation of telomerase homeostasis, which is controlled by a complex network of genes having inter-connected signals (191). Nowadays, other targets than telomerase and its regulation are becoming the subject of research, such as ESCRT system, a multi-protein complex, required for the formation of transport vesicles within the cell, critical for safeguarding proper TL maintenance.…”
Section: Future Perspectives and Other Therapiesmentioning
confidence: 99%
“…[10] In recent years, more and more studies have suggested that DNA methylation can be used as a biomarker for tumor diagnosis, treatment, risk stratification, and evaluation of prognosis . [1118] In this study, the methylation level of the hTERT promoter region in melanoma tissues was detected by BSP combined with the TA clonal sequencing method, and the methylation status of each CpG site in the target fragment was detected with high reliability and accuracy. [19]…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate the molecular mechanism exerted by TSY-1 on telomerase activity, in a recent study, Yu and colleagues treated the human leukemia cells HL60, the healthy donor-derived human PBMCs, and the blood CD34+ HSCs with TSY-1 (31.2 and 62.5 μ g/mL) for 24 h. They found that TSY-1 increased telomerase activity in normal blood mononuclear and in CD34+ HSCs; on the contrary, in the HL60 cell line, the authors observed an inhibition of telomerase activity. The opposite effects of TSY-1 on telomerase activity in normal and cancer cells correlated with the different number of positive SA- β -Gal staining cells and may be related to a different epigenetic modulation of the TERT promoter which, in turn, resulted in a different expression of TERT gene and protein [ 164 ].…”
Section: Herb-derived Products With An Antiaging and Antisenescentmentioning
confidence: 99%